2009
DOI: 10.1091/mbc.e07-10-1007
|View full text |Cite
|
Sign up to set email alerts
|

Katanin Knockdown Supports a Role for Microtubule Severing in Release of Basal Bodies before Mitosis inChlamydomonas

Abstract: Katanin is a microtubule-severing protein that participates in the regulation of cell cycle progression and in ciliary disassembly, but its precise role is not known for either activity. Our data suggest that in Chlamydomonas, katanin severs doublet microtubules at the proximal end of the flagellar transition zone, allowing disengagement of the basal body from the flagellum before mitosis. Using an RNA interference approach we have discovered that severe knockdown of the p60 subunit of katanin, KAT1, is achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 54 publications
(63 reference statements)
4
68
1
1
Order By: Relevance
“…The increased cellular toxicity of both overt silencing or protein overexpression is compatible with this concept and may explain the difficulty in the katanin field in producing viable or longlasting cellular or animal models with katanin depletion [for example 33]. We find that KATNAL2s interact directly and independently with Nubp1 and Nubp2 AAA proteins.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The increased cellular toxicity of both overt silencing or protein overexpression is compatible with this concept and may explain the difficulty in the katanin field in producing viable or longlasting cellular or animal models with katanin depletion [for example 33]. We find that KATNAL2s interact directly and independently with Nubp1 and Nubp2 AAA proteins.…”
Section: Discussionsupporting
confidence: 66%
“…In Tetrahymena, katanin's severing selectivity for ciliary MTs may be based on specific tubulin post-translational modifications [14]. In Chlamydomonas, katanin is also responsible for deciliation [32], facilitated by the release of basal bodies from the ciliary axoneme through selective severing of MTs at the transition zone, in preparation for mitosis [33]. Ciliary-based Hedgehog signaling is compromised in fibroblasts derived from p80 katanin-null mouse embryos and in neocortical development of these animals, displaying severe microlissencephaly [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…zone (Rasi et al, 2009) (Fig. 5) -an activity that might mirror that of Kat-60L1 in the dendritic pruning described above.…”
Section: Katanin Regulates Cilia Biogenesis and Disassemblymentioning
confidence: 77%
“…In the green alga Chlamydomonas, several studies have suggested that katanin plays a role in the flagellar autotomy response to stress and in the release of basal bodies from the transition zone prior to mitosis (Lohret et al, 1998;Lohret et al, 1999;Rasi et al, 2009;Parker et al, 2010). We have shown that Chlamydomonas mutants with defects in the p80 subunit of katanin have no defects in mitosis or flagellar autotomy; rather, these mutants lack the central pair of microtubules (Dymek et al, 2004).…”
Section: Introductionmentioning
confidence: 70%
“…As a second method to potentially localize p60 in wild-type cells and to determine if p60 protein is expressed in the pf19 mutant, we obtained anti-p60 katanin antibodies provided by the Quarmby lab (Rasi et al, 2009). The anti-p60 serum did not recognize the tagged p60-GFP protein in whole cell extracts (supplementary material Fig.…”
Section: Pf19 Encodes the P60 Subunit Of Kataninmentioning
confidence: 99%